Groundwater engineering and geotechnique - Mohammed, Thamer Ahmed; Kim Huat, Bujang (Universiti Putra Malaysia Press, 2004)
This book comprises nine chapters designed to cover the syllabus of the subject of Groundwater Hydraulics with some theory and application which is considered important for civil engineers. Post graduate students, and researchers. Many topics covered in this book are useful for undergraduate students doing the Civil Engineering programme. Information on the history of groundwater, the geological formation of aquifers and groundwater utilisation is also included in this book.